2001
DOI: 10.1128/iai.69.3.1358-1363.2001
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characteristics of a Protective Monoclonal Antibody against Serotype A and C Lipooligosaccharides from Moraxella catarrhalis

Abstract: A monoclonal antibody (MAb), designated MAb 8E7 (immunoglobulin G3), specific for Moraxella catarrhalis lipooligosaccharide (LOS) was evaluated for its functional activity in vitro and in a mouse model of colonization. Enzyme-linked immunosorbent assay (ELISA) demonstrated that the MAb 8E7 could be prepared to a high titer against LOS of the homologous strain 035E, and that it had bactericidal activity. MAb 8E7 reacted with M. catarrhalis serotype A and C LOSs but not serotype B LOS, as measured by ELISA and W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 37 publications
0
35
0
Order By: Relevance
“…Fitzgerald et al showed that the bacterial adherence of M. catarrhalis might be mediated by carbohydrate moieties (12). Our previous study revealed that a specific anti-LOS monoclonal antibody significantly inhibits the adherence of M. catarrhalis to human epithelial cells (28). In this report, attachment to human epithelial cells by the kdtA mutant showed more than a 50% reduction in attachment to Chang or cervix epithelial cells while there was no reduction in attachment to lung epithelial cells.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Fitzgerald et al showed that the bacterial adherence of M. catarrhalis might be mediated by carbohydrate moieties (12). Our previous study revealed that a specific anti-LOS monoclonal antibody significantly inhibits the adherence of M. catarrhalis to human epithelial cells (28). In this report, attachment to human epithelial cells by the kdtA mutant showed more than a 50% reduction in attachment to Chang or cervix epithelial cells while there was no reduction in attachment to lung epithelial cells.…”
Section: Discussionmentioning
confidence: 66%
“…The OMV preparation was also applied since there was no detectable LOS in O35EkdtA whole-cell lysates. Western blot using a rabbit anti-LOS antibody was performed (28). For the composition analysis, 30 to 35 g of wet cells from O35E and O35EkdtA were prepared for LOS purification by phenol-water extraction (21) and then the phenol-chloroform-petroleum ether (PCP) method (17), due to the lack of LOS extracts from O35EkdtA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that LOS is important for the pathogenesis of other respiratory pathogens, such as Neisseria meningitidis and Haemophilus influenzae, aiding in adherence of the bacterium to the mucosal epithelium and in the destruction of the mucosal barrier (16,30,51,52). Some studies have demonstrated that the LOS of M. catarrhalis may also aid in adherence of this bacterium to epithelial cells, while other studies have indicated that LOS may elicit antibody production, suggesting that this major glycolipid has potential as a vaccine candidate (2,23,24,27).Previous studies using polyclonal antisera and structural analyses have identified three major LOS serotypes for M. catarrhalis (7-9, 21, 55). Clinical isolates were grouped into LOS serotypes A (60%), B (30%), and C (5%), with 5% of the strains unidentified (21,26,55).…”
mentioning
confidence: 99%
“…For many bacteria, adherence to epithelial surfaces contributes to the evasion of host clearance mechanisms (4,25,59). Previous studies with M. catarrhalis have identified UspA1 (32, 36), UspA2 (2, 8, 36), Hag (14,15,17,19,24,45,47; M. M. Holm and E. R. Lafontaine, unpublished data), lipooligosaccharide (24), OMPCD (49), and UspA2H (32) as potential adhesins. Of these, only UspA1 and UspA2H have been directly shown to mediate adherence to human cells (32,36).…”
mentioning
confidence: 99%